Hepatitis C virus and human T-lymphotropic virus coinfection: epidemiological, clinical, laboratory and histopathological features Coinfecção vírus da hepatite C-vírus linfotrópico de células T humanas: aspectos epidemiológicos, clínicos, laboratoriais e histopatológicos - Flávio Augusto Pádua Milagres; Maria Irma Seixas Duarte; Ana Teresa Viso; Aluisio Cotrim Segurado (Revista da Sociedade Brasileira de Medicina Tropical, 2009)
Twenty-four hepatitis C virus patients coinfected with human T-lymphotropic virus type 1 were compared with six coinfected with HTLV-2 and 55 with HCV alone, regarding clinical, epidemiological, laboratory and histopathological data. Fischer's discriminant analysis was applied to define functions capable of differentiating between the study groups (HCV, HCV/HTLV-1 and HCV/HTLV-2). The discriminant accuracy was evaluated by cross-validation. Alcohol consumption, use of intravenous drugs or inhaled cocaine and sexual partnership with intravenous drug users were more frequent in the HCV/HTLV-2 group, whereas patients in the HCV group more often reported abdominal pain or a sexual partner with hepatitis. Coinfected patients presented higher platelet counts, but aminotransferase and gamma-glutamyl transpeptidase levels were higher among HCV-infected subjects. No significant difference between the groups was seen regarding liver histopathological findings. Through discriminant analysis, classification functions were defined, including sex, age group, intravenous drug use and sexual partner with hepatitis. Cross-validation revealed high discriminant accuracy for the HCV group. Compararam-se 24 pacientes coinfectados pelos vírus da hepatite C/vírus linfotrópico de células T humanas do tipo 1 com 6 coinfectados por VHC/HTLV-2 e 55 infectados pelo VHC, no tocante a dados clínico-epidemiológicos, laboratoriais e histopatológicos. A análise discriminante de Fischer foi utilizada para definir funções capazes de diferenciar os grupos de estudo (VHC, VHC/HTLV-1 e VHC/HTLV-2). A acurácia discriminatória foi avaliada pelo por validação cruzada. O uso de álcool, drogas endovenosas, cocaína inalatória e a parceria sexual com UDEV foram mais freqüentes no grupo VHC/HTLV-2, enquanto queixa de dor abdominal e parceiro sexual com hepatite predominaram no grupo VHC. Os coinfectados apresentaram número maior de plaquetas, enquanto as aminotransferases e a gamaglutamiltranspeptidase foram mais altas no grupo VHC. Não houve diferença ...